Problematika Hak Atas Kewarganegaraan Kehormatan Honorary Citizenship Di Indonesia: Implementasi Dan Dampaknya - Deden Rafi Syafiq Rabbani (Faculty of Law, Universitas Pattimura, 2021)
The crucial problem in the context of honorary citizenship is related to the process of granting and the mechanism for obtaining special honorary citizenship status. This specificity has an impact on various important elements in regulating the citizenship of a country, both on the conditions, procedures for obtaining or granting mechanisms, to the enjoyment of the right to honorary citizenship. In Indonesia, through the presence of Law Number 12 of 2006 concerning the Citizenship of the Republic of Indonesia, the right to honorary citizenship is part of what is regulated in it. The aims of this paper include: First, to provide an analysis of the conception of honorary citizenship in citizenship law. Second, provide an analysis related to the implementation and impact of the regulation of honorary citizenship in Indonesia. Through a socio-legal approach and qualitative normative research accompanied by a comparative approach in the form of a micro comparison by looking at the substance and legal rules in detail, the results of the research are as follows: First, the concept of honorary citizenship can be seen through the dimensions of a country's citizenship regime based on legal arrangements, interests state, human rights factors and in state development, and the essential political values of a country. Second, with regard to the implementation and impact of the regulation of honorary citizenship in Indonesia, it affects 3 (three) conditions, namely (1) the conditions for obtaining honorary citizenship. (2) The authority to grant honorary citizenship. (3) In the context of losing honorary citizenship status status.